Implementasi Metode Topsis Dalam Pemilihan Tenaga Fasilitator Lapangan Pada Pembangunan Infrastruktur Di Provinsi Bengkulu - Helvi Ramadhanti Rossa; Jusuf Wahyudi; Prahasti Prahasti (Jurnal Media Infotama, 2025)
The selection of the right field facilitator is very important in supporting the success of infrastructure development in Bengkulu Province. One method that can be used to help the objective selection process is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method focuses on selecting the alternative that is closest to the positive ideal solution and conversely, the furthest from the negative ideal solution. This study aims to implement the TOPSIS method in selecting field facilitators that are in accordance with the predetermined criteria. The criteria used in this study include experience, technical skills, managerial abilities, and competence in the field of infrastructure. Data collected from various field facilitator candidates were then analyzed using the TOPSIS method to provide the best ranking based on their proximity to the ideal solution. The results of this study are expected to provide more effective and efficient recommendations in selecting field facilitators, so that they can support the smoothness and quality of infrastructure development in Bengkulu Province